2007
DOI: 10.1159/000107935
|View full text |Cite
|
Sign up to set email alerts
|

Growth Hormone Therapy for Short Children Born Small for Gestational Age

Abstract: Children born small for gestational age may demonstrate continued growth retardation, resulting in persistent short stature. In the majority of the cases, this is linked with abnormal growth hormone secretion and also abnormal insulin-like growth factor levels. This review discusses the treatment of such children with recombinant human growth hormone. It illustrates the importance of starting therapy early, the dose-dependent response, and the advantages of continuous therapy and describes safety consideration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 113 publications
1
17
0
4
Order By: Relevance
“…Results here also indicate that r-hGH therapy in children born SGA is well tolerated, supporting other reports that treatment-related AEs are rare in this patient population [20,21,22]. The treatment was well tolerated in both groups, with only 5 AEs reported by 3 children over year 4 of therapy.…”
Section: Discussionsupporting
confidence: 89%
“…Results here also indicate that r-hGH therapy in children born SGA is well tolerated, supporting other reports that treatment-related AEs are rare in this patient population [20,21,22]. The treatment was well tolerated in both groups, with only 5 AEs reported by 3 children over year 4 of therapy.…”
Section: Discussionsupporting
confidence: 89%
“…However, because of increased prevalence of metabolic disturbances and high blood pressure in adults born SGA [15,17,18,52-55], specific attention must be paid to glucose homeostasis and weight gain in short SGA children treated with GH. Previous studies have demonstrated that discontinuation of long-term GH treatment in SGA adolescents normalized insulin levels (both fasting and stimulated) after a significant increase during GH therapy [56,57]. …”
Section: Discussionmentioning
confidence: 99%
“…GH treatment does not appear to be associated with an increased risk of malignancy [57]. It is recommended that IGF-1 concentrations should be monitored and GH dose should be reduced in children with a plasma IGF-1 above +2 SD [58,59].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrated that GH treatment in short children born SGA results in normalization of height during childhood and adulthood, while untreated children show no improvement in growth [3,[26][27][28][29][30][31]. During GH treatment in children born SGA, there is a rapid increase in total IGF-I levels and a slower increase in IGFBP-3 levels [32].…”
Section: Small For Gestational Agementioning
confidence: 99%